POLITIK HUKUM TENTANG PERAN MAHKAMAH KONSTITUSI DALAM MELINDUNGI EKSISTENSI KESATUAN MASYARAKAT HUKUM ADAT DI INDONESIA - Anindyajati, Titis (Jurnal Masyarakat dan Budaya, 2017)
Abstract The implementation of the communities’ rights, including the right of the natural resources has not been consistent with the principles of the constitution, although the existences of entities of the adat law societies (Kesatuan Masyarakat Hukum Adat, or KMHA) have already recognised and guaranteed by the Constitution and have also been mentioned in various Laws regarding the natural resources. For that reason, the Constitutional Court through its decisions, which determines the legal policy of Constitutional Court exists to balance the power between the excecutives and the judicials. There are already various papers about the entities of the adat law societies, but none of it elaborate on how the Laws protects the rights of KMHA and the role of Constitutional Court in protecting its existences from the legal politics. Laws and regulations related to the rights of KMHA regarding the natural resources and Constitutional Courts decisions related to KMHA and the natural resources were used in this paper as research objects. In addition, a number of bibliography and primary law resources were also employed as the source of study. This research unveiled that since the issue of the Constitutional Court Decision No.35/PUU-X/2012, there have been numerous technical rules regulating the existence of KMHA explicitly. In the meantime, the Constitutional Court through its decisions, based on the philosophical, juridical and sociological considerations, have already produced landmark decisions regarding the important limitations to define KMHA. This was one of the main role of Constitutional Court to uphold the principles of Constitution. Abstrak Sejatinya pelaksanaan hak-hak KMHA, khususnya hak-hak di bidang Sumber Daya Alam (SDA) belum sejalan dengan amanat konstitusi, walaupun keberadaan Kesatuan Masyarakat Hukum Adat (KMHA) telah ditegaskan dalam konstitusi dan diturunkan melalui peraturan perundang-undangan terkait Sumber Daya Alam (SDA). Untuk itulah Mahkamah Konstitusi melalui putusan-putusannya yang melahirkan Politik Hukum Mahkamah Konstitusi hadir untuk menyeimbangkan kekuasaan antara eksekutif dan yudikatif. Penulisan tentang Masyarakat Hukum Adat sudah banyak, namun belum ada yang lebih spesifik menulis tentang bagaimana Peraturan perundang-undangan mengatur hak-hak Kesatuan Masyarakat Hukum Adat (KMHA) dan bagaimana kontribusi Mahkamah Konstitusi dalam melindungi eksistensi KMHA dari aspek politik hukum. Peraturan Perundang-undangan yang terkait dengan hak-hak KMHA di bidang Sumber Daya Alam dan Putusan-Putusan Mahkamah Konstitusi yang terkait dengan KMHA dan Sumber Daya Alam khususnya digunakan sebagai objek penelitian serta meneliti bahan-bahan pustaka dalam menganalisis dan mengkaji bahan hukum. Dalam penelitian ini ditemukan bahwa sejak adanya Putusan MK No.35/PUU-X/2012, banyak muncul peraturan-peraturan teknis yang mengatur lebih tegas tentang keberadaan KMHA. Sementara itu, Politik Hukum Mahkamah Konstitusi melalui putusan-putusannya yang berlandaskan filosofis, yuridis dan sosiologis melahirkan landmark decision mengenai batasan penting untuk mendefinisikan KMHA. Hal ini merupakan salah satu peran Mahkamah dalam menjalankan amanat konstitusi.